Probiotic supplementation for 24 weeks in patients with non-alcoholic steatohepatitis: the PROBILIVER randomized clinical trial - Silva-Sperb, Amanda Souza; Moraes, Helena Abadie; Barcelos, Samantha Thifani Alrutz; de Moura, Bruna Concheski; Longo, Larisse; Michalczuk, Matheus Truccolo; Cerski, Carlos Thadeu Schmidt; Uribe-Cruz, Carolina; da Silveira, Themis Reverbel; Álvares-da-Silva, Mário Reis; Dall’Alba, Valesca (Frontiers in Nutrition, 2024)
Background and aim Considering the increasing prevalence of non-alcoholic steatohepatitis (NASH) and treatment gaps, this study aimed to evaluate the effect of probiotic supplementation on liver function markers, nutritional status, and clinical parameters. Methods This double-blind, randomized clinical trial (ClinicalTrials.gov ID: NCT0346782) included adult outpatients with biopsy-proven NASH. The intervention consisted of 24 weeks of supplementation with the probiotic mix Lactobacillus acidophilus (1 × 109 CFU) + Lactobacillus rhamnosus (1 × 109 CFU) + Lactobacillus paracasei (1 × 109 CFU) + Bifidobacterium lactis (1 × 109 CFU), or placebo, twice a day. The following parameters were evaluated: demographic and clinical data, transient elastography (FibroScan), liver enzymes, NAFLD fibrosis score, fatty liver index, laboratory assessment, serum concentration of toll-like receptor-4 (sTLR-4) and cytokeratin 18 (CK-18), anthropometric data, dietary intake, and physical activity. Regarding data analysis, the comparison between the groups was based on the delta of the difference of each variable analyzed (value at the end of treatment minus the baseline value) using the t-test for independent samples or the Mann–Whitney U-test. Results Forty-four patients with NASH completed the trial (51.4 ± 11.6 years). At baseline, 87% of participants had a mild liver fibrosis degree on biopsy, normal values of liver enzymes, transient elastography values consistent with grade 1 fibrosis in both groups, increased waist circumference (WC), a BMI of 30.97 kg/m2, and 76% presented with metabolic syndrome (MetS). After the intervention, no differences were observed between the probiotic and placebo groups in terms of MetS, WC, BMI scores, or liver enzyme levels (p > 0.05 for all). The elastography values remained consistent with grade 1 fibrosis in both groups. Although CK-18 was reduced in both groups, a larger effect size was noted in the probiotic group (D = 1.336). sTLR-4 was also reduced in both groups, with no difference between groups (p = 0.885). Conclusion Intervention with probiotics in the early stages of NASH demonstrated no significant change in hepatic and clinical parameters. Clinical trial registration ClinicalTrials.gov, identifier NCT0346782.